Tradução e interpretação em língua de sinais: avanços e retrocessos na mediação entre surdo, intérprete e professor numa análise educacional - Ribeiro, Solange Dias (2024)
This research's main objective is to investigate the advances and setbacks of the profession of Educational Sign Language Interpreter Translator (TILSE): how the interaction between deaf people, interpreters and teachers took place, what are the difficulties and challenges in the educational environment, what this interaction relationship has been like since the regulation of Decree No. 5,626/05, from the welfare and volunteer status of TILSE's activities to the regulation of the profession with Law No. 12,319/10, with the increasingly growing demand for this professional, especially in the educational environment. This research will analyze articles that deal with the role of Libras interpreter translators, focusing on the educational context, within a time frame on TILSE's role in face-to-face teaching and its role in remote teaching because of the COVID-19 pandemic, how the process took place in these two teaching modalities, drawing a parallel between them. In-person teaching is the most common traditional model, in which the teacher, interpreter and deaf student are in the same physical space. The educational environment and all activities are handled in person; for a long time, this was the main teaching model; however, there are many challenges to be considered, even in this modality. In remote teaching, everyone is in a different place and the interaction takes place at a distance. It is important to understand how teachers, deaf students and interpreters dealt with the difficulties of this new reality and what teaching strategies were used. This study's main objective is to analyze, through the articles researched, the interaction between deaf people, interpreters, and teachers in in-person Education and Remote Education in the teachinglearning process. The methodology used was qualitative, focusing on the analysis of the natural environment through bibliographic analysis carried out with articles on the topic in a period between 2005 and 2022. Thus, the bibliographical survey was used as methodological instruments, initially a search was made for dissertations and articles from the various areas of activity of this professional, as the research matured, the focus became the role of the Libras Educational Interpreter Translator. The articles selected were the themes that address the educational interpreter, the criteria for selection were those articles from the main postgraduate programs, and best evaluated by CAPES. With the analyzes it becomes evident that the data collected needs to be considered in discussions about the education of the deaf and the quality of the work of Libras translators and interpreters, as these professionals are part of the national policy